The Role of Green Banking Implementation in Sharia Banking Performance from an Islamic Perspective - Fathihani; Randyantini, Vely; Saputri, Ika Puji (International Journal of Management and Business Intelligence, 2024)
The aim of this research is to determine the effect of implementing green banking on the profitability of Islamic commercial banks in Indonesia and the concept of green banking from an Islamic perspective. This research was conducted at Islamic commercial banks registered with the Financial Services Authority (OJK) for the 2016-2022 period. The population in this study consisted of 12 Islamic commercial banks. The sample selection used a non-probability sampling method with a purposive sampling technique and a sample of 8 Islamic commercial banks with 7 years of observation was obtained so that 56 research data were obtained. The hypothesis testing method in this research uses a panel data regression model with a Fixed Effect Model (FEM) approach using the EViews program. The urgency of this research is to see the impact of implementing green banking on Sharia banking performance, especially from an Islamic perspective. The research results show that Green Banking practices have a negative and insignificant effect on Sharia banking performance.